Roads of Destiny - Henry, O., 1862-1910 (Salt Lake City, UT : Project Gutenberg, 1999)
"Roads of Destiny" by O. Henry is a collection of short stories written during the early 20th century. The book explores themes of fate, chance, and the unexpected turns life takes, with a particular emphasis on how momentary decisions can significantly influence one's destiny. The opening story introduces David Mignot, a young poet who leaves his village after a quarrel with his love, Yvonne, aiming to pursue fame and fortune. The opening of "Roads of Destiny" presents David's ill-fated journey as he embarks on a path filled with unforeseen circumstances. Straying from his original route, he encounters a mysterious pair$1 (Ba gentleman and a lady$1 (Bwhose subsequent misfortunes draw him into an entangled situation. David's quick decision to aid them thrusts him into an unexpected marriage proposal warped by pressure from the powerful Marquis de Beaupertuys. Navigating themes of love, obligation, and the unpredictability of fate, this initial narrative sets the tone for O. Henry's characteristic irony, showcasing how one choice can alter the course of a life forever. (This is an automatically generated summary.)s
Roads of destiny -- The guardian of the accolade -- The discounters of money -- The enchanted profile -- "Next to reading matter" -- Art and the bronco -- Phoebe -- A doubled-dyed deceiver -- The passing of Black Engle -- A retrieved reformation -- Cherchez la femme -- Friends in San Rosario -- The fourth in Salvador -- The emancipation of Billy -- The enchanted Kiss -- A departmental case -- The renaissance at Charleroi -- On behalf of the management -- Whistling Dick's Christmas stocking -- The halberdier of the little Rheinschloss -- Two renegades -- The lonesome road.
Wikipedia page about this book: https://en.wikipedia.org/wiki/Roads_of_Destiny_(short_story_collection)
Release date is 1999-02-01
E-text prepared by John Bickers and Dagny and revised by Joseph E. Loewenstein, M.D.
Keywords: United States -- Social life and customs -- Fiction; Short stories, American